Meaningful Experience Of Motivation To Power Seller With Orientation On Consumer Satisfaction For Identification Of Employee Benefits In The Textile Sales In South Surabaya - Etin Puspitasari; Wulandari Harjanti (LPPM of NAROTAMA UNIVERSITY, 2017)
Purpose : How to influence meaningful experiences to motivate salespeople with an orientation on the identification Consumer satisfaction with the reward at the sales employee Textile in South Surabaya. Design/methodology/approach : The research approach used in this study is a quantitative approach, the research focuses on hypothesis testing. The data used is the data measured and will produce results that can be generalized. This study is causal because it will examine the influence between variables. Findings Based on the results of the regression analysis shows that the significance value (Sig) t is 0.025. Because the value (Sig) 0.025 t less than the level ? 5% (0.05), the satisfaction of reward (pay satisfaction) strengthening the influence of a meaningful experience (experienced meaningfulness) to motivate salespeople to make customer orientation significantly. Research limitations/implications : This study uses the sales advisor respondents. General job description of this section is to conduct the sale of textile unit according to the targets set, which includes the search for Consumers (prospecting), Negotiation, closing, administrative process of sales, delivery and complaint. Practical implications : A validity test is used to determine the extent of measuring instruments used actually measure what yang want to be measured. The test is performed using Pearson Product Moment Correlation. Originality/value : The results showed meaningful experience (experienced meaningfulness) significantly affect the motivation of salespeople to make customer orientation and satisfaction with rewards (pay satisfaction) strengthening the influence of meaningful experience (experienced meaningfulness) to motivate salespeople to make customer orientation significantly.